OsNF-YC10, a seed preferentially expressed gene regulates grain width by affecting cell proliferation in rice. (March 2019) - Jia, Shuzhao; Xiong, Yufei; Xiao, Peipei; Wang, Xin; Yao, Jialing
Highlights: OsNF-YC10 is highly expressed in endosperm and spikelet hull at late developmental stages. OsNF-YC10 is a nuclear protein showing transcription activation activity. Knockout and knockdown of OsNF-YC10 resulted in narrow, thin and light grains owing to decrease numbers of spikelet hull cells. OsNF-YC10 regulates grain width by affecting cell proliferation. Abstract: Grain size and shape are important factors in determining the grain yield. In this study, OsNF-YC10, a member of the NF-Y transcription factor family encoding a putative histone transcription factor, was cloned and characterized. qRT-PCR and mRNA in situ hybridization analysis revealed that OsNF-YC10 was highly expressed in endosperm and spikelet hull at late developmental stages. The results showed that OsNF-YC10 was a nuclear protein showing transcription activation activity. The osnf-yc10 lines, produced using CRISPR/Cas9 technology, showed narrow, thin and light grains. Cytological experiments revealed significantly reduced cell number of spikelet hull in osnf-yc10 lines compared with that in WT. Narrow, thin, and light grains were found consistently in OsNF-YC10 RNAi transgenic lines. Moreover, the number of cells decreased in the grain-width direction than WT. These results indicated that OsNF-YC10 plays an important role in determining grain size and shape. OsNF-YC10 was further revealed to influence the expression of GW8 (a positive regulator of grain width), GW7 (a negative regulator of grain width) and cell cycle-regulated genes CYCD4, CYCA2.1, CYCB2.1, CYCB2.2, E2F2 . Taken together, it is suggested that OsNF-YC10 regulates the grains size and shape by influencing the cell proliferation of spikelet hulls.